Communication latency reduction in wide area measurement control and protection system. Issue 4 (1st October 2016) - Rana, Ankur Singh; Thomas, Mini S.; Senroy, Nilanjan
Abstract: Latency in communication network is critical in wide area measurement control and protection (WAMCP) of large power networks, as it deteriorates the system performance. In this paper, the WAMCP communication network is analysed in the context of data latency for dedicated as well as shared topologies. In an attempt to increase the overall reliability of the WAMCP, new communication architecture is proposed. Also, different methods are discussed to reduce the latency values of WAMCP. In case of shared networks, two routing protocols have been compared—distance vector and link state routing protocols—for different scenarios in terms of link failures. The role of the phasor data concentrator (PDC) timeout settings in reducing the communication delay is also presented.